Climate Strategy Between Ambition and Realism - Wetenschappelijke Raad voor het Regeringsbele (Amsterdam University Press, 2007)
This seminal and challenging analysis of the current global climate change suggests three courses of action for solving the climate problem: adaptation to the changed climate, selection of worldwide hopeful strategies for mitigation until 2050 and international coordination necessary to implement these strategies.